Keragaan Hama, Penyakit, dan Musuh Alami pada Budidaya Padi Organik - Dini Yuliani; Sudir Sudir (Jurnal Agro, 2017)
Organic rice cultivation intents to minimize the use of inorganic fertilizers and chemical pesticides, but in fact not apart from the disruption of pests and diseases. The study aimed to determine the pests, diseases, and natural enemies on organic rice cultivation. The research was conducted at Screen Field of ICRR at WS 2015/2016 and DS 2016, using Split Plot research design with three replications. The main plot was varieties of: 1). Inpari 25, 2). Inpari 33, and 3). Sintanur. The sub-plot was application of leaf extract of: 1). Mindi, 2). Soursop, 3). Mahogany, and 4). Control. Applications were performed on 4, 6, 8, and 10 weeks after planting (WAP). Observations of pests, diseases, and natural enemies on 5, 7, 9, and 11 WAP as many as 20 clumps/plots. The results showed that varieties and leaf extract applications significantly affected on severity of stem rot disease at 5 and 7 WAP in WS 2015/2016. In the rainy season found Yellowing on Inpari 25 and Inpari 33 varieties. However, Sintanur was more resistant to Yellowing with LCC value on two growing seasons was highest compared to the other varieties. Sintanur had the lowest Cercospora Leaf Spot disease severity compared to the other varieties. The severity of disease generally increased with the age of rice increase, while the pest population density and natural enemies were fluctuate. The density of the pest was quite high in the control plot, while the natural enemy density was high enough in the application plots of Mindi, Mahogany, and Soursop extracts.